Transição do enchimento terciário para o encaixe fluvial quaternário na área de Vila Velha de Ródão (sector NE da Bacia do Baixo Tejo) - Cunha, Pedro Proença (2010)
The geomorphologic characteristics and lithostratigraphic units of the transition from the Tertiary filling stage to the Quaternary fluvial incision in the Vila Velha de Ródão area (Lower Tagus Basin, NE sector) are presented. Several morphodynamic episodes, which had an important tectonic control, were distinguished. The same main morphosedimentary processes can be identified in other areas of this important river basin. Five periods of Quaternary fluvial incision were characterized.